2021
DOI: 10.1159/000519917
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Nucleus of Thalamus Deep Brain Stimulation: A Clinical-Based Analysis of the Ideal Target in Drug-Resistant Epilepsy

Abstract: <b><i>Introduction:</i></b> Deep brain stimulation of the anterior nucleus of thalamus (ANT-DBS) is an approved procedure for drug-resistant epilepsy. However, the preferred location inside ANT is not well known. In this study, we investigated the relationship between stereotactical coordinates of stimulated contacts and clinical improvement, in order to define the ideal target for ANT-DBS. <b><i>Methods:</i></b> Individual contact’s coordinates were obtained in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…In the studies which followed the SANTE trial, the median seizure frequency reduction ranged from 50% to as much as 80.3%, with a responder rate exceeding 70-80% of patients [18,21,22,[24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42]. The outcomes of ANT DBS studies are set out in Table 1.…”
Section: Indications and Contraindications For Ant Dbsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the studies which followed the SANTE trial, the median seizure frequency reduction ranged from 50% to as much as 80.3%, with a responder rate exceeding 70-80% of patients [18,21,22,[24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42]. The outcomes of ANT DBS studies are set out in Table 1.…”
Section: Indications and Contraindications For Ant Dbsmentioning
confidence: 99%
“…Although the evidence for the clinical effectiveness of VNS and DBS exists, the exact mechanisms of action remain unexplained [37]. PET studies during VNS have shown increased cerebral bloodflow in the thalamus [44].…”
Section: Indications and Contraindications For Ant Dbsmentioning
confidence: 99%